Perancangan Sistem Informasi Perpustakaan Berbasis Website di SMA Kristen 1 Salatiga - Meilinda Novena Br Simanjuntak Br Simanjuntak; Rissal Efendi (Peneliti.net, 2023)
ibrary is one of the learning resources that every school or university must have. Having a web-based library information system that facilitates the management of borrowing or returning books so that the circulation of borrowed books can be properly recorded during optimization Borrowing and returning books is very risky in the traditional system because there are often delays in finding books, books are lost, or the information needed is stored carelessly. With the development of information technology, library information systems can be integrated into web-based information systems, which can be one way to overcome the problem of managing detailed information on library books so that they can be used by the wider community. Based on a needs analysis, users can access the library information system from anywhere to see what book information is in the library, making it easier to find book information to borrow or return.